Foundations of modern slavery : profiles of unfree and coerced labor through the ages - Dowlah, C. A. F. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This is a rigorous academic inquiry into how labor power has been dehumanized and commodified around the world through the ages for creation of wealth, capital accumulation, and industrialization. Major forms of unfree and involuntary labor markets around the world-from slavery to serfdom, from feudalism to indentured servitude, from guestworker programs to human-trafficking-have been analyzed theoretically and empirically from multidisciplinary and comparative perspectives. The inquiry encompasses the slaveries of the Amerindians and the Africans in the New World in the context of the European colonization; the worlds of serfdom and feudalism in the contexts of Western Europe, Eastern Europe, Russia, Japan, China, and India; the episodes of indentured servitude of the Europeans in the New World prior to African slavery, and that of the Indians and the Chinese after the abolition of African slavery; the worlds of guestworker programs in the United States and Europe in the post-World War II era and the migrant labor programs of the Gulf Region since the 1970s; and the slavery-like practices in the contemporary world, including forced labor in global supply chains. The book is designed not only for students and academia in labor economics, labor history, and global socio-economic and political transformations, but also for the intelligent and inquiring general readers, policy makers, and reformers across the disciplinary pursuits of Economics, Political Science, History, Sociology, Anthropology, and Law"--
Keywords: Slavery -- History; Commodification -- History; Land tenure -- History; Labor market -- History; BUSINESS & ECONOMICS / Labor; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / Theory